Use of Qualitative Research Methods in Natural Resources Management Studies: Sharing of Some Anthropological Experiences from the Ethnographic Study of Two Indigenous Irrigation Systems from Western Terai - Uprety, Laya Prasad (Nepalese Journal of Qualitative Research Methods, 2009)
doi: 10.3126/njqrm.v1i0.1969 Keywords: Ethnographic Study; Natural Resources Management Nepalese Journal of Qualitative Research Methods Vol.1 2007 pp.1-20